Detection of Inducible Clindamycin Resistance in Beta-Hemolytic Streptococci by Using the CLSI Broth Microdilution Test and Erythromycin-Clindamycin Combinations - Bowling, Jason E. (American Society for Microbiology (ASM), 2010)
This study assessed an erythromycin-clindamycin (ERY-CC) broth test for inducible CC resistance in beta-hemolytic streptococci. One hundred one isolates of groups A, B, C, F, and G were tested by the CLSI broth microdilution method. Combinations of 1 and 0.25 μg/ml or 0.5 and 0.25 μg/ml of ERY and CC, respectively, detected all inducible isolates.